Implementation of self interaction free density functional methods and applications to dilute magnetic semiconductors - Pemmaraju, Sri Chaitanya Das (Trinity College (Dublin, Ireland). School of Physics, 2008)
The present thesis mainly deals with the implementation of self interaction free density functional methods in a numerically efficient density functional theory code SIESTA and the application of the said methods in ab-inito electronic structure calculations. We present calculations on the polarizability of molecular chains using explicity orbital dependent density functional methods viz., exact exchange and self interaction corrected (SIC) functionals, which address some long standing issues in the field. We show that SIC functionals in fact perform better than the exact exchange functional at the KLI level of approximation. We discuss the ASIC method which is an approximate self interaction correction scheme that is computationally in-expensive. Results for finite systems as well as extended systems are discussed. We then discuss the electronic and magnetic structure of defective Hafnium Oxide systems where in we show that native Hafnium vacancies exhibit spin polarized ground states with ferromagnetic inter-defect coupling. An extensive study on Co doped ZnO is then presented mainly focusing on the possibility for intrinsic ferromagnetism in the material arising from native defect induced perturbations to the electronic structure of doped Co. We show that a defect-dopant complex center formed form a substitutional Co ion and an Oxygen vacancy can mediate long range ferromagnetic interactions. However we attribute the experimentally observed signatures of ferromagnetism to blocked superiparamagnetic clusters. Finally we present ab-initio electronic transport calculations on Mn12 based single molecule magnets in a two terminal device set up. The current-voltage (I-V) characteristics of the molecule for two different spin configurations of the Mn12 center are studied. We show that a change in the local magnetic configuration on the molecule can lead to a detectable change in the I-V characteristics.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin